AN ANALYSIS OF SLANG TRANSLATIONIN THE SUBTITLE OF "AIRHEADS" FILM - Mona Salwa Saraswati, - (2008)
The title of this paper is 'AN ANALYSIS OF SLANG TRANSLATION IN THE SUBTITLE OF "AIRHEADS" FILM'. This study presents an analysis the types of slang that are found in the film, and the subtitling strategies used in the film. This paper employs a qualitative approach in analyzing the available data. This research also uses a descriptive method in presenting the data. In analyzing the subtitle of the film, the writer conducts several steps. The writer transfers the film dialogue and subtitle into a script. In this research, the writer determines the slang types by using Willis' classification (1964:195) and Feldman and Sourdot's classification (2008), then the writer determines the subtitling strategy of the translation by using Gottlieb's strategy of subtitling (2000). The findings reveal slang words which are categorized into the classifications of Willis (slang which give new meaning to a standard word and slang which are new creation words), and Feldman and Sourdot (Syntactic procedure, lexical procedure, formal procedure, semantic procedure). The writer also finds that there are eight subtitling strategies used in this film's subtitle, namely: transfer, decimation, paraphrase, deletion, condensation, resignation, dislocation, and expansion. However, the most frequently used is the transfer strategy. The writer also finds some mistranslations in the subtitle of the "Airheads" film. The findings of this study are expected to give a wider horizon about slang words, and also can add and enrich the knowledge about slang and its translation. Furthermore, it will give some fresh ideas for further study in this research